Hair-to-Hair Trichoscopy: An Objective Method to Assess Effectiveness of Botulinum Toxin in a Clinical Trial for Androgenetic Alopecia - Melo, Daniel Fernandes; Donda, André Luiz Vairo; de Almeida, Rita Fernanda Cortez; Antelo, Daniela Alves Pereira; Muller-Ramos, Paulo [UNESP]; Machado, Carla Jorge; Frattini, Sidney; Tosti, Antonella; Barcaui, Carlos Baptista (My University, 2024)
Introduction: Androgenetic alopecia (AGA) is the most common alopecia affecting both genders leading to a potential decrease in quality of life and self-esteem. A current concern in trichology is how to accurately measure clinical response in both daily medical practice and academic research. Hair-to-hair (H2H)-matching technology™ has recently emerged as a technique to evaluate variations in follicular units, hair shaft number, and thickness. This study aimed to describe the methodology employed in a clinical trial using this technology to test the efficacy of botulinum toxin (BT) for male AGA. Methods: This pilot study is a triple-blind, randomized, split scalp, placebo-controlled clinical trial. Patients enrolled were submitted to injections half of the scalp with 50 IU of BT and the other half with 1 mL of normal saline as a control. The trial involved three visits (weeks 0, 12, and 24) and 8 global clinical photographs followed by H2H-matching trichoscopy were captured before the injections at each visit. Paired t test analysis was employed for matched pairs of the following parameters: total hair count, the total number of terminal hair strands, average shaft thickness, and the number of hairs lost or gained during each visit. Then, the software compared the differences between the two sides (BT vs. placebo) per scalp zone and a long time. Conclusion: The combination of manually corrected image processing, follicular map, and H2H-matching technology™ appears to be the most precise way to evaluate changes in hair count and thickness over time. The design is reproducible and can help other researchers and dermatologists in their clinical practice to obtain reliable results in similar scientific research.
Keywords: Alopecia; Androgenetic alopecia; Botulinum toxin; Hair count; Hair-to-hair matching